Wheatgrass ameliorates glycerol-induced nephrotoxicity via regulation of NF-kB p65/KIM-1/NGAL signaling pathway - Nahed A. Raslan; Hend Helal; Amany Balah; Ahmed M. El-Dessouki; Azza A. Ali (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Acute kidney injury (AKI) is closely associated with rhabdomyolysis (RM), characterized by tubular damage and cell death through altered pyroptotic signaling pathways. This study aimed to explore the efficacy of Wheatgrass (WG) as a potential protective agent in ameliorating nephrotoxicity caused by glycerol-induced oxidative stress (OS) in rats, emphasizing the involvement of nuclear factor kappa p65 (NF-kB p65)/kidney injury molecule-1 (KIM-1)/neutrophil gelatinase-associated lipocalin (NGAL) signaling pathway. Methods RM induction was achieved via a single intramuscular administration of 50% v/v glycerol dissolved in 0.9% saline solution (10 ml/kg), following a 6-h period of water deprivation. WG was administered daily at 75 mg/kg for 7 days prior to glycerol administration in the WG-pretreated groups. Renal function, OS, inflammatory, and tubular injury markers were assessed using Enzyme-Linked Immunosorbent Assay. Histopathological and immunohistochemical analyses were conducted to evaluate renal structural changes and NF-kB p65 expression. Results The glycerol-injected group exhibited significant increases in renal injury markers (blood urea nitrogen, serum creatinine, creatine kinase) and elevations in NGAL, KIM-1, malondialdehyde, interleukin-6, and interleukin-18 levels, alongside decreased activity of antioxidant enzymes (glutathione transferase, superoxide dismutase, catalase) (p < 0.001). Moreover, immunohistochemical analysis indicated a heightened expression level of NF-kB p65, correlating with the observed histopathological alterations, which confirmed renal tubular degeneration, inflammation, and vascular alterations. However, WG pretreatment markedly reduced the concentrations of biomarkers associated with oxidative and renal damage, alongside evident decrease in the levels of inflammatory markers. Additionally, a significant restoration in immunohistochemical and histopathological changes was noted. Conclusions These findings demonstrate that WG holds notable protection against glycerol-induced acute kidney injury by mitigating OS and inflammation, particularly through NF-kBp65/KIM-1/NGAL pathway modulation. The observed biochemical and histological improvements highlight WG’s potential as a natural therapeutic candidate for AKI, warranting further clinical exploration.